GENDER AND THE MEDIA - ROSALIND GILL (U S A POLITY PRESS, 2007)
How have advertisers responded to feminism? What should we make of the popularity of 'lad mags'? Is news a gendered product? Are men's bodies - as much as women's - new objectified in the media? Do shows like Oprah or Jerry Springer redraw the boundary between public and private? Is chick lit rewriting the romance? These are just some of the questions addressed in Gender and the Media.
Keywords: Mass Media -- Women in Mass Media -- Advertising